Validation of a questionnaire to assess stress, tobacco use, physical activity, and dietary supplementation - Diene da Silva Schlickmann; Gabriela Cristina Uebel; Patrícia Molz; Eliane Aparecida Castro; Caroline dos Santos; Pedro Jose Benito; Silvia Isabel Rech Franke (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2023)
Introduction: Given the large expansion of gyms, reliable instruments are needed to assess and obtain information about the behavior of gym members, and these instruments may be able to assist in the implementation of planning and health promotion strategies in this population. Objective: To develop and validate a questionnaire to assess the lifestyle habits, physical activity, and dietary supplementation of gym members. Materials and Methods: A 44-item questionnaire was developed. The Delphi technique was used for content and appearance validity using the content validity index (CVI). Construct validity was verified by exploratory factor analysis (EFA) in several phases. Reliability analysis was assessed by internal consistency and temporal reproducibility using Cronbach's alpha and the intraclass correlation coefficient (ICC), respectively. Results: Two rounds of the Delphi technique identified a total CVI of 100%. The final model was composed of eight items, with excellent quality in the EFA adjustment, and distributed into four factors. Internal consistency was adequate in all factors, with ICC 0.997, 0.916, 0.698, and 0.631. Conclusions: This study provides a reliable and valid questionnaire to assess stress, smoking, physical activity, and dietary supplementation of fitness center members.